BREAKING ROMANCE CONVENTIONS: HERO/HEROINE DYNAMICS IN ROWELL’S ELEANOR & PARK - Adzkia, Fara Maulina; Furaida, Asni (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
This study examines Eleanor & Park, a contemporary romance novel by Rainbow Rowell, through the lens of Janice Radway's ideal romance formula. The novel portrays two central characters, Eleanor and Park, whose relationship deviates from traditional romance norms, offering a fresh perspective on love and identity. The objective of this paper is to explore how Rowell's characterization of the hero, Park, and the heroine, Eleanor, aligns with or challenges the conventional ideals of romance characters as outlined by Radway. Eleanor embodies traits of the ideal heroine—she is intelligent, spunky, and independent—while Park, although strong and caring, does not fully fit the traditional masculine hero image. This deviation from the typical hero archetype, combined with Eleanor's struggles and vulnerability, challenges the stereotypical gender roles typically found in romance novels. The study adopts a New Criticism approach, focusing on intrinsic elements of the text, particularly characterizations and plot structure, without considering external influences such as the author's biography or social context. The analysis finds that the characters' roles in the story push against traditional boundaries, as Eleanor's resilience and emotional depth redefine the notion of the ideal heroine, while Park’s more sensitive and less traditionally masculine traits complicate the idealization of the romantic hero. Furthermore, the novel’s plot emphasizes emotional growth, mutual understanding, and empathy over dominance or stereotypical gender dynamics. The open-ended conclusion of the story further subverts the expectations of a conventional romance, presenting the relationship as a tool for personal development rather than a perfect, idealized union. In doing so, the novel offers a more nuanced portrayal of teenage relationships, highlighting their impermanence and complexity. Ultimately, Eleanor & Park invites readers to reconsider conventional romance narratives by focusing on the internal growth and emotional connections between characters rather than adhering to formulaic depictions of love. This study contributes to a broader understanding of contemporary romance novels and their potential for depicting more diverse, realistic, and empowering portrayals of love and identity.